Concise Synthesis of Capuramycin - Kurosu, Michio (Org Lett, 2009)
A concise total synthesis of capuramycin (1), a promising preclinical TB drug lead, is achieved by high-yield formations of the cyanohydrin 5a and 4″,5″-glycal derivative 12. Capuramycin can be synthesized in eight steps from the uridine building block 5a with >30% overall yield. The synthetic intermediates reported here are useful for generation of analogs to improve pharmacokinetic properties of capuramycin.